Neljän maan parlamenttihistorian vertailua - Kujala, Antti (Historiallinen Aikakauskirja, 2018)
Arvosteltu teos: The springs of democracy: National and transnational debates on constitutional reform in the British, German, Swedish and Finnish Parliaments, 1917-1919 / Pasi Ihalainen. Helsinki : Finnish Literature Society, SKS, 2017.